Medication utilisation trends during pregnancy and factors influencing adverse pregnancy outcomes in patients with rheumatoid arthritis - Sun-Young Jung; Yoon-Kyoung Sung; Soo-Kyung Cho; Dae Hyun Yoo; Yeo-Jin Song; Eunwoo Nam; Yu-Seon Jung; Jihyun Keum (RMD Open)
Objectives We aimed to investigate medication utilisation trends during pregnancy and identify factors associated with adverse pregnancy outcomes (APOs) in patients with rheumatoid arthritis (RA).Methods Female patients with RA aged 20–50 years were identified from the Korean national health insurance database between 2010 and 2020. Pregnancy episodes were divided into two groups according to pregnancy outcome: the delivery group and the APO group (abortion and stillbirth). The characteristics and medication utilisation patterns were compared between the two groups, and multivariable logistic regression analysis was conducted to identify the factors associated with APOs.Results A total of 5728 pregnancy episodes were included, comprising 4576 delivery episodes and 1152 APO episodes. The mean maternal age for all pregnancy episodes was 33.7 years; 33.3 years in the delivery group and 33.7 years in the APO group. Hydroxychloroquine was the most commonly used conventional synthetic disease-modifying antirheumatic drug (DMARD) during the preconception period and pregnancy in both groups. The prescription rate of all DMARDs decreased rapidly during pregnancy. In the multivariable analysis, use of methotrexate (adjusted OR (aOR): 2.14, 95% CI 1.57 to 2.92) and leflunomide (aOR: 2.68, 95% CI 1.39 to 5.15) within 3 months before conception was associated with APOs.Conclusion Methotrexate and leflunomide are associated with an increased possibility of APOs, emphasising the importance of appropriate medication adjustment when planning for pregnancy.